Korelasi antara Disiplin Belajar dan Motivasi Belajar dengan Hasil Belajar dalam Pembelajaran Tematik Kelas V Sekolah Dasar Negeri 24 Pontianak Tenggara di Masa Pandemi COVID-19 - Kurniawati, Aisyah (Innovative: Journal Of Social Science Research, 2024)
This study aims to describe the level of correlation between Learning Discipline and Learning Motivation with Learning Outcomes in Thematic Learning of Grade V of State Elementary School 24 Southeast Pontianak during the Covid-19 Pandemic. The method used in this research is descriptive method with correlation study research form. The population in this study were all fifth grade students of SDN 24 Southeast Pontianak. The sampling used in this study used Saturated Sampling with a total sample of 40 grade V students of SDN 24 Southeast Pontianak. Data collection techniques used in this study are indirect communication techniques and measurement techniques. Indirect communication techniques were used to collect data on learning discipline and learning motivation with instruments in the form of questionnaires while measurement techniques were used to collect data on learning outcomes of grade V students of SDN 24 Southeast Pontianak. The data analysis technique carried out by statistical analysis shows that at an error rate of 5%, the magnitude of the correlation between learning discipline and learning motivation with student learning outcomes rcount of 0.700 with an rtable of 0.312. Because rcount> rtable, it can be concluded that there is a positive relationship between learning discipline and learning motivation together with student learning outcomes in thematic learning during the Covid-19 pandemic.